TEACHING ENGLISH TO FUTURE SPECIALISTS IN PRESCHOOL EDUCATION - Makarova, Natalia (Publishing house «UKRLOGOS Group», 2024)
The integration of Ukrainian education into the global educational space has led to the fact that foreign language communication becomes an essential component of future professional activity. There is a need to teach children a foreign language starting from preschool age. The advisability of teaching MI to preschool children is discussed on the pages of scientific journals and at scientific conferences.